A new big data approach based on geoecological information-modeling system. Issue 1 (22nd December 2017) - Varotsos, Costas A.; Krapivin, Vladimir F.
Abstract: In this paper, the geoecological information-modeling system (GIMS) is described as possible improvement of the Big Data approach. The main GIMS function is the use of algorithms and models that capture the fundamental processes controlling the evolution of the climate–nature–society (CNSS) system. The GIMS structure includes 24 blocks that realize a series of models and algorithms for global big data processing and analysis. The CNSS global model is the basic block of the GIMS. The operational tools of GIMS are demonstrated by examining several scenarios associated with the reconstruction of forest areas. It is shown that significant impacts on forests can lead to global climate variations on a large scale.